1997
DOI: 10.3327/jnst.34.1153
|View full text |Cite
|
Sign up to set email alerts
|

Change in Sorption Characteristics of Uranium during Crystallization of Amorphous Iron Minerals.

Abstract: Sorption behavior of uranium (VI) during crystallization of amorphous iron (A.Fe) minerals to crystalline iron (C.Fe) minerals have been investigated. Two different sorption conditions are applied for the experiments. One is the condition in which uranium is sorbed on A.Fe minerals before the crystallization (dynamic condition). The other is the condition in which uranium is sorbed on the A.Fe minerals and C.Fe minerals of goethite (static condition). Associations of uranium with the iron minerals are examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…The desorption rate of U from laboratory-spiked pristine materials (Fuhrmann et al, 1997;Ohnuki et al, 1997;Giammar and Hering, 2001) and U-contaminated sediments (Braithwaite et al, 1997;Mason et al, 1997) was found to decrease with increasing exposure time to uranium contamination. For example, desorption equilibrium of U(VI) from goethite after aging for 1 month was achieved rapidly, but much slower desorption was observed after aging for 6 months (Giammar and Hering, 2001).…”
Section: Introductionmentioning
confidence: 92%
“…The desorption rate of U from laboratory-spiked pristine materials (Fuhrmann et al, 1997;Ohnuki et al, 1997;Giammar and Hering, 2001) and U-contaminated sediments (Braithwaite et al, 1997;Mason et al, 1997) was found to decrease with increasing exposure time to uranium contamination. For example, desorption equilibrium of U(VI) from goethite after aging for 1 month was achieved rapidly, but much slower desorption was observed after aging for 6 months (Giammar and Hering, 2001).…”
Section: Introductionmentioning
confidence: 92%
“…Uranium is not thought to be incorporated into the α-FeOOH (goethite) structure (GERTH, 1990). However, studies report the uptake of U during the formation of crystalline and amorphous Fe oxides (OHNUKI et al, 1997;PLOTNIKOV and BANNYKH, 1997;SATO et al, 1997;BRUNO et al, 1995).…”
Section: Introduction-the Geochemical Speciation Of Uranium Influencementioning
confidence: 99%
“…Uranium sorption and co-precipitation processes with Fe minerals are studied in lieu of repository assessment, nuclear waste treatment and U biogeochemistry (MOYES et al, 2000;OHNUKI et al, 1997;PLOTNIKOV and BANNYKH, 1997;SATO et al, 1997;HOBBS and KARRAKER, 1996;BRUNO et al, 1995;PEARCY et al, 1994;WAITE et al, 1994 and many others). As part of the Poços de Caldas natural analogue study (Brazil), researchers evaluated the co-precipitation and precipitation equilibrium of U(VI) with Fe(III) oxides (BRUNO et al, 1995).…”
Section: Implications Of Findings To the Geologic Environmentmentioning
confidence: 99%
“…Similarly, Sato et al (1997) reported that the decreasing trend of U content in Fe-(hydr)oxide nodules corresponds to the order of decreasing crystallinity of Fe oxides at the Koongarra U ore deposit site, Australia. Ohnuki et al (1997) also extracted U that had been From the observed facts, we can deduce that the amorphous phases may initially be prominent at immediate uptake of U over their surfaces, but there could be a lack of tight bounding between them due to their low structural stability, leading U to be desorbed during geologic time. Thus, it is not easy for some accumulated U to be found in them.…”
Section: U Sorption Mechanismmentioning
confidence: 91%